Electrochemical Cross‐Electrophile‐Coupling for Transition‐Metal‐Free Allylic Carboxylation with Ambient CO2. Issue 21 (14th November 2022) - Zhao, Rong; Lin, Zhipeng; Maksso, Isaac; Struwe, Julia; Ackermann, Lutz
Abstract: The use of CO2 as a C1 building block to access carboxylic acids is one of the key aspects in the context of carbon capture and utilization (CCU). Herein we report on an electrochemical carboxylation of allyl esters with CO2 at atmospheric pressure. This strategy enabled to the synthesis of diverse carboxylic acids without the need for a transition metal catalyst. Furthermore, the mechanism was studied through ICP‐MS analysis and cyclic voltammetry studies for the cross‐electrophile CO2 coupling. Abstract : Electrochemical carboxylation of allyl esters was achieved in the presence of CO2 at atmospheric pressure, enabling the synthesis of diverse branched and linear carboxylic acids without transition metal catalyst. The mechanism was investigated through ICP‐MS analysis and cyclic voltammetry studies.